Evolution of the industry structure of the dried plums market - Stoneman, Katharine Renee (Kansas State University, 2012)
The objective of this analysis is to derive several econometric estimates of the Panzar-Rosse statistic of industry structure in order to determine whether the dried plums market resembles that of a firm collusion (monopoly or tightly structured oligopoly), a hybrid of monopolistic and competitive tendencies (monopolistically competitive), or perfectly competitive. The result of the Panzar-Rosse test is the H-Statistic: the sum of all elasticities of a firm’s total revenue with respect to factor prices focusing on the long run equilibrium. This study looks at data from a previous study conducted by Alston et al (1998) that includes firm level data for three of the participating firms in the dried plums industry from September 6, 1992 through July 7, 1996 and data provided from Sunsweet Cooperative encompassing firm level data from six firm participants from July 20, 2008 through June 13, 2010. Ordinary least squares regression equations were estimated to determine the elasticities of firm level input costs and other exogenous variables. A total of four regression equations per data set were tested in order to compile the necessary information for the formulation of the Panzar-Rosse H-Statistic. Adjusting for econometric concerns, overall the results show an H-Statistic commensurate with that of an industry that is operating as monopolistically competitive. In examining the evolution of firm-level changes from the time period of the first data set to that of the second, the results suggest the industry, while remaining monopolistically competitive, has also become more competitive; a finding consistent with the decreased concentration noted in the industry over time.
Keywords: Monopolistic Competition; Prunes; California agriculture; Monopoly; Economics, Agricultural (0503)